A high-strength composite plastic film and preparation method thereof
By introducing nanoparticles into plastic films and using chemical grafting and surface coating technology, the problem of insufficient strength and wear resistance of traditional plastic films is solved, and the preparation of high-strength composite plastic films is realized to meet high-performance needs and maintain high-performance Lightweight properties.
Patent Information
- Application Number
- CN202411087993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-09
AI Technical Summary
Traditional plastic films have shortcomings in strength and wear resistance, and are difficult to meet high performance needs, such as aerospace and deep-sea detection, and traditional enhancement methods increase material weight and cost.
By introducing nanoparticles as reinforcement, the nanoreinforcing agent is surface modified by chemical grafting and surface coating technology to improve its compatibility with the basic plastic material, and the nanoreinforcing agent is realized through ultrasonic and melt blending technology. Evenly disperse to form a high-strength composite plastic film.
It significantly improves the mechanical strength and wear resistance of composite plastic films, maintains lightweight properties, meets high performance needs, and reduces material weight and cost.
Smart Images

Figure CN118599211B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of film materials, in particular to a high-strength composite plastic film and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology and the acceleration of industrialization, plastic film materials are increasingly used in various fields including packaging, construction, automobiles, and electronics. However, traditional plastic film materials often have certain limitations in performance, especially in terms of strength, wear resistance, and heat resistance. These performance deficiencies are particularly prominent in fields that require strict material performance, including aerospace, deep-sea exploration, and precision instrument packaging.
[0003] Traditional plastic films are mostly made of basic plastic materials including polyethylene (PE), polypropylene (PP), and polyvinyl chloride (PVC). Although these materials have good processing properties and certain strength, their strength and wear resistance are often difficult to meet actual needs in application scenarios with high requirements for material performance, including heavy-load packaging and high-strength building materials. In addition, traditional reinforcement methods, including increasing the thickness of the material or using polymer composite materials, can improve the mechanical strength of the plastic film, but will also increase the weight and cost of the material, reducing its practicality and economic benefits.
[0004] In view of the above situation, it is necessary to optimize the existing composite plastic film and its preparation method, by introducing nanoparticles as reinforcing agents and utilizing the surface effect and volume effect of nanoparticles to improve the mechanical strength and wear resistance of the composite plastic film. Therefore, developing a high-strength composite plastic film and its preparation method is of great significance to improving the performance of plastic films and meeting practical application needs. Summary of the invention
[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and to provide a high-strength composite plastic film and a preparation method thereof. By introducing nanoparticles as reinforcing agents and utilizing the surface effect and volume effect of the nanoparticles, the mechanical strength and wear resistance of the composite plastic film are significantly improved. Nano-enhancement technology enables the plastic film to maintain its light weight while greatly improving its strength, meeting the needs of fields with strict requirements on material properties.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: On the one hand, a method for preparing a high-strength composite plastic film, the steps of the preparation method are:
[0007] S100, raw material preparation: prepare basic plastic materials and nano-enhancers in a certain proportion;
[0008] S200, dispersion treatment of nano-enhancer: using a chemical grafting method to perform surface modification treatment on the nano-enhancer so that its surface carries functional groups similar to those of the basic plastic material to improve the compatibility between the two, performing surface coating treatment on the grafted nano-enhancer, using a coating agent to interact with the surface of the grafted nano-enhancer to form a stable coating, and using a high-speed mixer or a ball mill to mix the modified nano-enhancer with the basic plastic material so that the nano-enhancer is preliminarily dispersed in the basic plastic material, and placing the preliminarily mixed materials into an ultrasonic dispersion device so that the nano-enhancer is further uniformly dispersed in the basic plastic material through the action of ultrasonic waves;
[0009] S300, melt blending: placing the dispersed mixture into a melt blending device, heating it to a molten state, and fully mixing the base plastic material and the nano-enhancer;
[0010] S400, molding process: preparing the melt-blended mixture into a nano-enhanced high-strength composite plastic film through a molding process of extrusion, calendaring, and film blowing;
[0011] S500, cooling and curing: cooling and curing the formed plastic film to keep stable performance.
[0012] Further, the S100 includes:
[0013] S101, determine the ratio of the base plastic material and the nano-enhancement agent according to the performance requirements and cost considerations of the target product;
[0014] S102, using a precise electronic scale, weigh out the required basic plastic material and nano-enhancer respectively;
[0015] S103, check whether the weighed material meets the quality standards, including color, purity, and particle size.
[0016] Furthermore, the specific steps of performing surface coating treatment on the grafted nano-enhancer in S200 are:
[0017] (1) Select the coating agent based on the properties of the nanoreinforcement agent and the target base plastic material;
[0018] (2) dispersing the grafted nano-reinforcement agent in a solution of a coating agent, and uniformly covering the surface of the nano-reinforcement agent with the coating agent by stirring and ultrasonic dispersion;
[0019] (3) curing the coated nano-enhancer so that the coating layer is firmly attached to the surface of the nano-enhancer;
[0020] (4) The morphology and thickness of the coating layer were detected by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to evaluate its modification effect and compatibility with the base plastic material.
[0021] Furthermore, the specific steps of evaluating the compatibility of the S200 with the base plastic material through the compatibility test are as follows:
[0022] (1) Mixing the modified nano-reinforcement agent with the base plastic material to prepare a test sample;
[0023] (2) Check whether the mixture is uniform and whether there is obvious phase separation and agglomeration. Observe whether the mixture remains stable after standing for a period of time without stratification or precipitation to ensure uniform mixing so as to accurately evaluate compatibility;
[0024] (3) Measure the viscosity of the mixture and compare it with the viscosity of the pure plastic material to evaluate the effect of the addition of the nanoreinforcement agent on the fluidity, and examine the mechanical properties of the mixture to evaluate the performance improvement effect of the nanoreinforcement agent on the plastic;
[0025] (4) Use infrared spectroscopy (FTIR) technology to analyze the chemical bonding in the mixture to confirm whether there is a chemical interaction between the nanoreinforcer and the plastic material. Use thermogravimetric analysis (TGA) to evaluate the thermal stability of the mixture and understand the effect of the nanoreinforcer on the thermal properties of the plastic.
[0026] (5) Observe the microstructure of the mixture using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to check the dispersion of the nanoreinforcement agent in the plastic matrix and whether it forms an interface with the plastic matrix;
[0027] (6) Conduct long-term aging tests on the mixture to observe changes in its performance to evaluate the long-term compatibility of the nanoreinforcement agent with the plastic material;
[0028] (7) Record and analyze data: Record the data and observations of each test in detail, compare the performance data before and after modification and the performance data of mixtures with different ratios, and analyze the effect of nano-reinforcement on the compatibility of plastic materials.
[0029] Furthermore, the S300 includes:
[0030] S301, preheating the melt blending equipment to ensure that the material can quickly reach a molten state in the equipment;
[0031] S302, adding the dispersed mixture into a melt blending device;
[0032] S303, heating the mixture in the equipment to make it reach a molten state, and the melting temperature and time should be adjusted according to the type and performance of the basic plastic material;
[0033] S304, in a molten state, the base plastic material and the nano-enhancer are fully mixed by stirring or shearing action of the equipment.
[0034] Furthermore, the S400 includes:
[0035] S401, select the appropriate molding method according to the shape and size requirements of the product;
[0036] S402, adjusting the temperature, pressure and speed parameters of the equipment according to the selected molding method and product requirements;
[0037] S403, the melt-blended mixture is processed into a desired shape and size through a molding device. During the molding process, the uniformity and stability of the material should be ensured.
[0038] Furthermore, the S500 includes:
[0039] S501, select the appropriate cooling method according to the material and shape requirements of the product;
[0040] S502, during the cooling process, controlling the cooling rate to avoid internal stress or deformation of the product;
[0041] S503, controlling the temperature and time to fully solidify the plastic film to achieve stable performance;
[0042] S504, inspect the produced plastic film to ensure that it meets the production requirements.
[0043] Furthermore, the S504 measures the thickness of the plastic film using a manual measuring tool, performs a tensile strength test using an intelligent electronic tensile testing machine TST-02H, and performs a thermal stability test using a thermal gravimetric analysis (TGA). Through the above testing methods, the performance and quality of the nano-enhanced high-strength composite plastic film can be comprehensively evaluated to ensure that it meets the predetermined performance standards and customer requirements.
[0044] Compared with the prior art, the high-strength composite plastic film and its preparation method have the following beneficial effects:
[0045] 1. The present invention introduces a nano-enhancer and uses chemical grafting and surface coating methods to perform surface modification on the nano-enhancer so that it is evenly dispersed and tightly combined in the basic plastic material, thereby improving the mechanical strength of the composite plastic film. At the same time, the nanoparticles can fill the microscopic defects in the basic plastic material to form a denser material structure, which not only enhances the mechanical strength of the plastic film, but also improves its wear resistance. When used for a long time or subjected to friction and wear, the nanoparticles can effectively resist wear and maintain the surface flatness and performance stability of the plastic film.
[0046] 2. The present invention achieves a significant improvement in material performance while maintaining the lightweight characteristics of the plastic film by adopting nano-enhancement technology. The density of nanoparticles is much lower than that of traditional reinforcing materials, and its reinforcement effect is more significant. Therefore, the mechanical strength and wear resistance of the composite plastic film can be greatly improved without increasing the weight of the material.
[0047] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0049] Figure 1 The present invention is a process flow chart of a method for preparing a high-strength composite plastic film.
[0050] Figure 2 The present invention is a flow chart of a method for preparing a high-strength composite plastic film. DETAILED DESCRIPTION
[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0052] This embodiment describes in detail a method for preparing a high-strength composite plastic film, by introducing nanoparticles as reinforcing agents and utilizing the surface effect and volume effect of the nanoparticles to improve the mechanical strength and wear resistance of the composite plastic film.
[0053] For the raw material preparation stage (S100), according to the performance requirements of the target product, including strength, wear resistance, weather resistance and cost considerations, the selected material ratios are: polyethylene (PE): 60%, polypropylene (PP): 30%, polyvinyl chloride (PVC): 10%, carbon nanotubes (CNTs): 1%, nano silicon oxide (SiO2NPs): 0.5%. Use an electronic scale accurate to two decimal places to weigh out the required basic plastic materials and nano-enhancers respectively, ensuring that the weighing error of each material does not exceed 0.1%. Perform quality checks on the weighed materials, including color, purity and particle size, to ensure that the materials are free of impurities, have uniform color, and meet the particle size standards.
[0054] For the dispersion treatment stage of the nano-reinforcer (S200), the nano-reinforcers (CNTs and SiO2NPs) are surface-modified by chemical grafting and surface coating. The purpose of this step is to make the surface of the nano-reinforcers (CNTs and SiO2NPs) have functional groups similar to those of the basic plastic materials, improve the compatibility of the nano-reinforcers with the basic plastic materials, and prevent agglomeration during subsequent processing. The grafted nano-reinforcers are surface-coated. According to the properties of the nano-reinforcers and the target basic plastic materials, a coating agent is selected, and the grafted nano-reinforcers are dispersed in a solution of the coating agent. The coating agent is evenly covered on the surface of the nano-reinforcers by stirring and ultrasonic dispersion. The coated nano-reinforcer is cured so that the coating layer is firmly attached to the surface of the nano-reinforcer. This step is intended to further increase the affinity between the nano-reinforcer and the basic plastic material to ensure that the nano-reinforcer can be evenly dispersed in the basic plastic material. A high-speed mixer is used to preliminarily mix the modified nano-reinforcer with the basic plastic material (PE, PP, PVC). The mixing time is set to 10 minutes to ensure that the nano-reinforcer is preliminarily dispersed in the basic plastic material. The preliminarily mixed materials are placed in an ultrasonic dispersion device. Through the action of ultrasonic waves, the nano-reinforcer is further evenly dispersed in the basic plastic material. The ultrasonic dispersion time is set to 30 minutes, and the power is adjusted according to the equipment model and experimental conditions.
[0055] For the melt blending stage (S300), the dispersed mixture is placed in a melt blending device and heated to a molten state (180°C). During the heating process, it is necessary to continuously stir to ensure that the mixture is evenly heated. In the molten state, the mixture is continued to be stirred to fully mix the base plastic material and the nano-enhancer. The mixing time is set to 20 minutes to ensure that the mixture reaches a uniform state.
[0056] In the molding process stage (S400), the mixture after melt blending is molded through an extruder, and a suitable mold and extrusion speed are selected according to product requirements to prepare a nano-enhanced high-strength composite plastic film. During the extrusion process, the plastic film is cut and stretched as needed to adjust its size and shape.
[0057] For the cooling and curing stage (S500), the formed plastic film is placed in a cooling device for cooling. The cooling temperature and time are adjusted according to product requirements to ensure that the plastic film maintains stable performance. During the cooling process, the plastic film gradually solidifies. The solidified plastic film has high strength and wear resistance and can meet various application requirements.
[0058] In summary, through the above embodiments, a high-strength composite plastic film can be prepared, and the plastic film has excellent performance and good application prospects. Example 2
[0059] This example illustrates in detail how a high-strength composite plastic film and its preparation method optimize the compatibility of nano-enhancers with basic plastic materials.
[0060] For the raw material preparation stage, polyethylene (PE) was selected as the basic plastic material due to its good physical properties and wide application fields. Carbon nanotubes (CNTs) were selected as nano-reinforcement agents to improve the mechanical properties of PE. According to experimental requirements, the ratio of PE to CNTs was determined to be 95:5 (weight ratio) to ensure that the amount of CNTs added was sufficient to produce a significant reinforcement effect while maintaining the basic properties of PE.
[0061] For the dispersion treatment stage of the nano-enhancer, first, plasma treatment is used to activate the surface of the nano-enhancer to generate reaction sites for the grafting reaction. Specifically, nitrogen gas is introduced into the plasma treatment equipment, and the gas is excited by electric field and radio frequency to generate plasma. The nano-silicon oxide that has been cleaned and dried is placed in the plasma treatment area to fully expose its surface to the plasma. The active particles in the plasma will collide and interact with the surface of the nano-silicon oxide, resulting in the breaking and recombination of the surface chemical bonds to form new active sites. Reactive groups are introduced on the surface of the nano-enhancer so that its surface has functional groups similar to PE, thereby improving the compatibility between the two and the polyethylene with active end groups and the polyethylene with active end groups. Its derivatives are grafted onto carbon nanotubes through an amidation reaction, wherein the active groups on polyethylene and its derivatives react with the carboxyl functional groups on the surface of the carbon nanotubes to form covalent bonds. On the basis of chemical grafting, CNTs are surface coated with a silane coupling agent. This step is intended to further increase the affinity between CNTs and PE and ensure that CNTs can be evenly dispersed in PE. According to the characteristics of PE and CNTs, a silane coupling agent is selected, and CNTs are mixed with a surfactant for coating. After coating, the CNTs are dried and sieved to remove excess surfactants and impurities. The coated CNTs are cured so that the coating layer is firmly attached to the surface of the CNTs.
[0062] For the compatibility test, an infrared spectrometer is used to analyze the chemical bonding of the modified CNTs and PE mixture. By comparing the infrared spectra of CNTs and PE before and after modification, the chemical bonding between CNTs and PE can be understood, thereby evaluating the compatibility of the two. A thermogravimetric analyzer is used to evaluate the thermal stability of the mixture. By measuring the mass change of the mixture at different temperatures, the thermal stability between CNTs and PE can be understood, and the compatibility of the two can be further evaluated. A scanning electron microscope is used to observe the microstructure of the mixture. By observing the dispersion of CNTs in PE and the interface bonding state, the compatibility of the two can be intuitively evaluated.
[0063] In the melt blending stage, the dispersed CNTs and PE are added into a melt blender in a predetermined ratio, and melt blended under high temperature and stirring conditions to ensure that the CNTs are evenly dispersed in the PE and form a good interface bond with the PE.
[0064] In the molding process stage, the mixture after melt blending is molded by an injection molding machine or other molding equipment to obtain the desired plastic product.
[0065] During the cooling and curing stage, the molded plastic product is placed under appropriate temperature and humidity conditions for cooling and curing to ensure the dimensional stability and performance of the product.
[0066] In summary, through the above embodiments, the compatibility of the nano-reinforcement agent CNTs and the basic plastic material PE can be successfully optimized to obtain a plastic product with excellent mechanical properties.
[0067] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a high-strength composite plastic film, characterized in that: The steps of the preparation method are: S100, raw material preparation: preparing a basic plastic material and a nano-enhancer according to a certain ratio, wherein the basic plastic includes polyethylene, and the nano-enhancer includes carbon nanotubes; S200, dispersion treatment of nano-enhancer: using plasma treatment to activate the surface of carbon nanotubes, generating reaction sites for grafting reaction, grafting polyethylene and its derivatives with active end groups onto carbon nanotubes through amidation reaction, wherein the active groups on polyethylene and its derivatives react with the carboxyl functional groups on the surface of carbon nanotubes to form covalent bonds, introducing reactive groups on the surface of nano-enhancers so that their surface carries functional groups similar to those of polyethylene, thereby improving the compatibility between the two, selecting silane coupling agents based on the characteristics of polyethylene and carbon nanotubes on the basis of chemical grafting, using silane coupling agents to perform surface coating treatment on carbon nanotubes, mixing carbon nanotubes with surfactants for coating treatment, The coating agent is used to interact with the surface of the grafted nano-enhancer to form a stable coating, further increase the affinity between the carbon nanotubes and the polyethylene, and ensure that the carbon nanotubes can be evenly dispersed in the polyethylene. After the coating is completed, the carbon nanotubes are dried and screened to remove excess surfactants and impurities. The coated carbon nanotubes are cured to make the coating layer firmly attached to the surface of the carbon nanotubes. The modified nano-enhancer is mixed with the basic plastic material using a high-speed mixer or a ball mill to preliminarily disperse the nano-enhancer in the basic plastic material. The preliminarily mixed materials are placed in an ultrasonic dispersion device to further evenly disperse the nano-enhancer in the basic plastic material through the action of ultrasonic waves. S300, melt blending: placing the dispersed mixture into a melt blending device, heating it to a molten state, and fully mixing the base plastic material and the nano-enhancer; S400, molding process: preparing the melt-blended mixture into a nano-enhanced high-strength composite plastic film through a molding process of extrusion, calendaring, and film blowing; S500, cooling and curing: cooling and curing the formed plastic film to keep stable performance.
2. The method for preparing a high-strength composite plastic film according to claim 1, characterized in that: The S100 includes: S101, determine the ratio of the base plastic material and the nano-enhancement agent according to the performance requirements and cost considerations of the target product; S102, using an electronic scale to weigh out the required basic plastic material and nano-enhancer respectively; S103, check whether the weighed material meets the quality standards, including color, purity, and particle size.
3. The method for preparing a high-strength composite plastic film according to claim 1, characterized in that: The specific steps of the S200 for surface coating the grafted nano-enhancer are as follows: (1) Select the coating agent based on the properties of the nanoreinforcement agent and the target base plastic material; (2) dispersing the grafted nano-reinforcement agent in a solution of a coating agent, and uniformly covering the surface of the nano-reinforcement agent with the coating agent by stirring and ultrasonic dispersion; (3) curing the coated nano-enhancer so that the coating layer is firmly attached to the surface of the nano-enhancer; (4) The morphology and thickness of the coating layer were detected by scanning electron microscopy and transmission electron microscopy, and its modification effect and compatibility with the base plastic material were evaluated.
4. The method for preparing a high-strength composite plastic film according to claim 3, characterized in that: The specific steps of the S200 compatibility assessment are: (1) Mixing the modified nano-reinforcement agent with the base plastic material to prepare a test sample; (2) Check whether the mixture is uniform and whether there is obvious phase separation and agglomeration. Observe whether the mixture remains stable after standing for a period of time without stratification or precipitation to ensure uniform mixing so as to accurately evaluate compatibility; (3) Measure the viscosity of the mixture and compare it with the viscosity of the pure plastic material to evaluate the effect of the addition of the nanoreinforcement agent on the fluidity, and examine the mechanical properties of the mixture to evaluate the performance improvement effect of the nanoreinforcement agent on the plastic; (4) Use infrared spectroscopy to analyze the chemical bonding in the mixture to confirm whether there is a chemical interaction between the nanoreinforcer and the plastic material. Use thermogravimetric analysis to evaluate the thermal stability of the mixture and understand the effect of the nanoreinforcer on the thermal properties of the plastic. (5) Observe the microstructure of the mixture using a scanning electron microscope or a transmission electron microscope to check the dispersion of the nanoreinforcement agent in the plastic matrix and whether it forms an interface with the plastic matrix; (6) Conduct long-term aging tests on the mixture to observe changes in its performance to evaluate the long-term compatibility of the nanoreinforcement agent with the plastic material; (7) Record and analyze data: Record the data and observations of each test in detail, compare the performance data before and after modification and the performance data of mixtures with different ratios, and analyze the effect of nano-reinforcement agents on the compatibility of plastic materials.
5. The method for preparing a high-strength composite plastic film according to claim 1, characterized in that: The S300 includes: S301, preheating the melt blending equipment to ensure that the material can quickly reach a molten state in the equipment; S302, adding the dispersed mixture into a melt blending device; S303, heating the mixture in the equipment to make it reach a molten state, and the melting temperature and time should be adjusted according to the type and performance of the basic plastic material; S304, in a molten state, the base plastic material and the nano-enhancer are fully mixed by stirring or shearing action of the equipment.
6. The method for preparing a high-strength composite plastic film according to claim 1, characterized in that: The S400 includes: S401, select the molding method according to the shape and size requirements of the product; S402, adjusting the temperature, pressure and speed parameters of the equipment according to the selected molding method and product requirements; S403, the melt-blended mixture is processed into a desired shape and size through a molding device. During the molding process, the uniformity and stability of the material should be ensured.
7. The method for preparing a high-strength composite plastic film according to claim 1, characterized in that: The S500 includes: S501, select the appropriate cooling method according to the material and shape requirements of the product; S502, during the cooling process, controlling the cooling rate to avoid internal stress or deformation of the product; S503, controlling the temperature and time to fully solidify the plastic film to achieve stable performance; S504, inspect the produced plastic film to ensure that it meets the production requirements.
8. The method for preparing a high-strength composite plastic film according to claim 7, characterized in that: The S504 measures the thickness of the plastic film using a manual measuring tool, performs a tensile strength test using an intelligent electronic tensile testing machine, and performs a thermal stability test using a thermogravimetric analysis. Through the above testing methods, the performance and quality of the nano-enhanced high-strength composite plastic film are comprehensively evaluated to ensure that it meets the predetermined performance standards and customer requirements.
9. A high-strength composite plastic film, characterized in that: The high-strength composite plastic film is prepared by the preparation method of any one of claims 1 to 8, wherein the material composition of the plastic film is: Basic plastic material: constitutes the main body of the composite plastic film and provides the basic performance and morphology of the plastic film; Nano-enhancers: include carbon nanotubes, with particle sizes ranging from 1 to 100 nanometers.
Citation Information
Patent Citations
Graphene oxide coating film as well as preparation method and application thereof
CN111349258A